2008
DOI: 10.3233/jad-2008-14305
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of the Inhibitory Synapse Scaffolding Protein Gephyrin in Alzheimer's Disease

Abstract: Excitotoxicity may contribute to neuronal and synaptic loss in Alzheimer's disease (AD). Aberrant levels of gephyrin, a post-synaptic receptor-stabilizing protein, could affect the inhibitory modulation of excitatory impulses. We assayed gephyrin protein in two brain areas susceptible to neuronal loss in AD, and in a spared area, in autopsy tissue from normal subjects (n = 15) and AD patients (n = 15). Quantification was by in-gel immunodetection against known concentrations of a recombinant truncated gephyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 37 publications
4
41
1
Order By: Relevance
“…Previous reports have shown reduced gephyrin expression in AD (14), although direct comparison to our study is difficult because of differences in brain homogenate preparation. The choice of Agarwal et al to use a non-detergent-extracted method with low-speed spin likely led to a reduction in the soluble protein analyzed, whereas in our work, a reduction in gephyrin expression is supported by a loss of gephyrin immunoreactivity in neuronal processes (Figure 1) and by quantitative proteomic analysis.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Previous reports have shown reduced gephyrin expression in AD (14), although direct comparison to our study is difficult because of differences in brain homogenate preparation. The choice of Agarwal et al to use a non-detergent-extracted method with low-speed spin likely led to a reduction in the soluble protein analyzed, whereas in our work, a reduction in gephyrin expression is supported by a loss of gephyrin immunoreactivity in neuronal processes (Figure 1) and by quantitative proteomic analysis.…”
Section: Discussioncontrasting
confidence: 68%
“…Their data suggest that in AD, there is a loss of GABA receptor association with gephyrin, a main organizer of the inhibitory synapse. Similarly, Agarwal and colleagues suggest gephyrin expression is reduced in AD (14). These results implicate proteins that maintain the integrity of the inhibitory synapse, like gephyrin, in AD pathogenesis.…”
Section: Introductionmentioning
confidence: 91%
“…Interestingly, hippocampal areas largely affected by plaques and tangles show reduced immunoreactivity for α1 and γ2 and upregulation of γ1/3 subunits in the neuropil (9,36), changes similar to the subunit expression profile in temporal cortex found in our study. Although principal GABA A R subunits were reduced in the AD brain, Gephyrin was similar between AD and control groups, probably as a result of compensatory increments of Gephyrin at advanced stages of AD (37). Interestingly, the strong correlations between Gephyrin and GABA A R subunits mRNAs in the control group were lost in the AD group, suggesting disruptions of Gephyrin-dependent clustering of GABA A Rs, and encouraging future studies focusing on the structure of GABAergic synapses in AD.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, the cholinergic hypothesis of AD assumes a particular susceptibility of cholinergic neurons (reviewed in Q1 Bartus et al, 1982;Auld et al, 2002), reflecting a primary affection of cholinergic terminals in cortical regions early in AD (Hu et al, 2003). More recently, several studies have suggested a particular vulnerability of glutamatergic synapses Kirvell et al, 2006;Kashani et al, 2008;Minkeviciene et al, 2008;Proctor et al, 2010), whereas other studies have instead reported that it is GABAergic neurons that are initially affected in early AD (Agarwal et al, 2008;Baglietto-Vargas et al, 2010;Verret et al, 2012).…”
Section: Introductionmentioning
confidence: 97%